2007
DOI: 10.1590/s1516-35982007000400020
|View full text |Cite
|
Sign up to set email alerts
|

Variações diárias nas excreções de creatinina e derivados de purinas em novilhos

Abstract: Objetivou-se estimar as variações nas excreções diárias de creatinina, uréia e derivados de purinas (DP) na urina utilizando coletas durante seis dias consecutivos e avaliar as concentrações de nitrogênio uréico no plasma (NUP) em novilhos. Utilizaram-se quatro animais, machos castrados, de grau de sangue predominantemente Holandês, peso médio de 445 kg, distribuídos em quadrado latino 4 x 4, com os tratamentos definidos em esquema fatorial 2 x 2 (dois níveis de uréia em substituição ao farelo de soja: 0 e 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
3
2
1
3
Order By: Relevance
“…In the present study, the proportion of allantoin in relation to total purines was 94.05%. Leal et al (2007) and Rennó et al (2002) observed that the mean value of this proportion in cattle was 92.2 and 91.7%, respectively, which corroborates the results obtained in this study. Oliveira (2008) has commented that CBM supplemented with calcium oxide influences the greater availability of essential nutrients and higher efficiency in their use by ruminal microbiota, which was not observed in this study.…”
Section: Ruminal Microbial Nitrogenous Compounds Estimated From Urinasupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the proportion of allantoin in relation to total purines was 94.05%. Leal et al (2007) and Rennó et al (2002) observed that the mean value of this proportion in cattle was 92.2 and 91.7%, respectively, which corroborates the results obtained in this study. Oliveira (2008) has commented that CBM supplemented with calcium oxide influences the greater availability of essential nutrients and higher efficiency in their use by ruminal microbiota, which was not observed in this study.…”
Section: Ruminal Microbial Nitrogenous Compounds Estimated From Urinasupporting
confidence: 92%
“…The mean creatinine excretion value observed by Rennó et al (2000) in 4 experiments with cattle weighing approximately 238 kg of BW reported mean values of 27.36 mg kg − 1 BW. In another study conducted by Leal et al (2007) using cattle with approximately 445 kg of BW, found urinary creatinine excretion of 25.47 mg kg − 1 BW. Chizzotti (2004), using Holstein heifers, developed an equation to estimate daily urinary creatinine excretion (CE) in relation to BW, where CE (mg kg − 1 BW) = 32.27 − 0.01093 BW.…”
Section: Ruminal Microbial Nitrogenous Compounds Estimated From Urinamentioning
confidence: 96%
“…The mean ALA:PD ratio was 0.983 g/g, which is close to the value reported by Leal et al (2007) of 0.922. According to Verbic (1990), excretion of allantoine may represent 0.850g/g of the total purine derivatives.…”
Section: Resultssupporting
confidence: 86%
“…Microbial production was lower than the 130 g CP kg TDN −1 reported by NRC (1996) and120 g 130 g CP kg TDN −1 by Leal et al (2007).…”
Section: Resultscontrasting
confidence: 57%